A Kaleckian approach to financialization and functional income distribution: Austria and Finland in comparative perspective - Cara Dabrowski; Sonia Kuhls (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2024)
In this paper, we examine if and to what extent the Kaleckian theory of mark-up pricing can explain changes in functional income distribution in an environment of financialization. Following this approach, we expect financialization to influence the aggregate wage share through three channels: (1) sectoral recomposition, (2) financial overhead costs and rentiers' profits claims, and (3) bargaining power of trade unions and workers. We empirically analyze the long-term trends for each of the channels before and after the Great Financial Crisis and the Great Recession for Austria and Finland. Overall, we find evidence for all three re-distributional channels contributing to the changes in functional income distribution. The explanatory power of the individual channels, however, differs strongly due to the heterogeneity of the countries.
Keywords: D31; D33; D43; 330; Finance-dominated capitalism; financialization; distribution; financial and economic crisis; Kaleckian theory of distribution